Análisis de la influencia del clima en la producción de la Musa acuminata-AAA piurana, 2000-2019 - Oballe Neyra, Carlos Enrique (2024)
This study investigates the analysis of the influence of climate on the production of Musa acuminata-AAA in Piura from 2000 to 2019. For the research, the SARIMAX (Seasonal AutoRegressive Integrated Moving Average with exogenous regressors) approach was used, which is an extension of the ARIMA model, on a multiple quadratic econometric model to analyze the effect of the harvested area, maximum temperature, minimum temperature, precipitation and relative humidity on the production of Musa acuminata-AAA piurana. Through its concave or convex shape, the study uses the multiple quadratic econometric model to demonstrate the negative alteration of production when climatic variables are outside their thresholds, and to determine the level of significance of each exogenous variable over the endogenous one. The results show that production is negatively impacted by the presence of relative humidity and high surface temperature of previous months, and positively impacted by precipitation and maximum temperature. All variables have significance with p-value less than 0.05.